2016
DOI: 10.3389/fncel.2016.00115
|View full text |Cite
|
Sign up to set email alerts
|

Brain State-Dependent Closed-Loop Modulation of Paired Associative Stimulation Controlled by Sensorimotor Desynchronization

Abstract: Background: Pairing peripheral electrical stimulation (ES) and transcranial magnetic stimulation (TMS) increases corticospinal excitability when applied with a specific temporal pattern. When the two stimulation techniques are applied separately, motor imagery (MI)-related oscillatory modulation amplifies both ES-related cortical effects—sensorimotor event-related desynchronization (ERD), and TMS-induced peripheral responses—motor-evoked potentials (MEP). However, the influence of brain self-regulation on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 96 publications
2
26
0
Order By: Relevance
“…The spectral power range for feedback was chosen on the basis of our previous findings. These had indicated that the effective corticospinal connectivity is mediated in this frequency band (Kraus et al, 2016b, Royter and Gharabaghi, 2016, Raco et al, 2016), which also correlated with subsequent motor gains (Naros et al, 2016). Moreover, movement-related desynchronization in the ipsilesional sensorimotor cortex is compromised in stroke patients compared to healthy controls, i.e., the more severe the patient's motor impairment, the less beta-band desynchronization (Rossiter et al, 2014).…”
Section: Methodsmentioning
confidence: 98%
“…The spectral power range for feedback was chosen on the basis of our previous findings. These had indicated that the effective corticospinal connectivity is mediated in this frequency band (Kraus et al, 2016b, Royter and Gharabaghi, 2016, Raco et al, 2016), which also correlated with subsequent motor gains (Naros et al, 2016). Moreover, movement-related desynchronization in the ipsilesional sensorimotor cortex is compromised in stroke patients compared to healthy controls, i.e., the more severe the patient's motor impairment, the less beta-band desynchronization (Rossiter et al, 2014).…”
Section: Methodsmentioning
confidence: 98%
“…It is then just a natural step to try and incorporate available models of synaptic plasticity to underpin the desired adaptive behavior of neuroprosthetic or BCI systems; the involved strategies for closed-loop, real-time hybrid system, and the associated development of "neuromorphic" chips, also have potential to possibly augment PAS, endowing them with adaptive capabilities. In the PAS domain, such options just begin to be considered (Royter et al, 2016;Sabathiel et al, 2016); in the following, to provide a hint at available methodologies to make progress towards closed-loop, adaptive PAS systems, we first briefly touch upon the present status of implementable synaptic plasticity models, and next…”
Section: Section 4: Prospects In Neuromorphic Circuitsmentioning
confidence: 99%
“…The results of this study showed that for the APB muscle, corticospinal excitability after application of MI‐PAS25 was significantly increased relative to that observed after performance of MI alone. Two previous studies have shown that corticospinal excitability induced by PAS25 is increased by concurrent application of MI (Kraus, Naros, Guggenberger, Leao, & Ziemann, ; Royter & Gharabaghi, ). Although the interstimulus interval between PAS25 and MI differed (i.e., MI followed by PAS25 vs. MI and PAS25 concurrently applied), all interventional protocols produced similar effects through the associative pairing of the different stimuli.…”
Section: Discussionmentioning
confidence: 92%